Connecting a Mother's Knowledge About Nutrition with the Nutritional Status of Toddlers in the Village of Troso, Subdistrict Karanganom, Klaten - Lusinta Agustina; Dewi Susilowati (Genius Midwifery Journal, 2023)
Introductions: Toddlers still experience problem nutrition by 17.7%. The nutritional status of a baby is a crucial matter that every individual should know. If malnutrition occurs during the critical early years, it can lead to irreversible characteristics that cannot be fixed. In Klaten Regency itself, the recorded percentage is as high as 7.3% for toddlers still experiencing nutritional problems, which is 1.9% higher than the regional average in Central Java. Aims: To learn about the connection between a mother's nutrition and the nutritional status of toddlers in the village of Troso, Subdistrict Karanganom, Klaten Regency. Methods: We conducted research using an analytic correlational approach with a cross-sectional study design. The sampling technique employed was cluster random sampling, resulting in a sample size of 70 respondents of mothers of toddlers from the Village of Troso in the Karanganom Subdistrict, Klaten Regency. The data were analyzed using the Spearman Rank test with a significance level set at 0.05. Results: The study revealed that 32 respondents (45.7%) who possessed good knowledge also had toddlers with good nutritional status. The Spearman rank test yielded a correlation coefficient of 0.476, which was statistically significant at p < 0.05. Conclusions: There is a connection between the level of knowledge of Mothers with nutritional status toddlers in the Village Troso Subdistrict Karanganom Regency Klaten.